A Simple Disk Stacking Plus Micro-Elution Method for Rapid Detection of the Synergistic Effect of Aztreonam and Ceftazidime/Avibactam Against Metallo-β-Lactamase Producing Enterobacterales - Liu Z; Hang X; Yan T; Chu W; Gong Z; Liu Y; Dai Y; Yang M; Li J; Zhou Q (Infection and Drug Resistance, 2023)
Zhou Liu,1,* Xiubing Hang,1,* Tao Yan,1 Wenwen Chu,1 Zhen Gong,1 Yanyan Liu,2– 4 Yuanyuan Dai,5 Min Yang,6 Jiabin Li,2– 4 Qiang Zhou1 1Department of Laboratory Medicine, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 2Department of Infectious Diseases, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China; 3Anhui Center for Surveillance of Bacterial Resistance, Hefei, Anhui, People’s Republic of China; 4Institute of Bacterial Resistance, Anhui Medical University, Hefei, Anhui, People’s Republic of China; 5Department of Laboratory Medicine, Anhui Provincial Hospital, Hefei, Anhui, People’s Republic of China; 6Department of Intensive Care, The Second Affiliated Hospital of Anhui Medical University, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Yang, Department of Intensive Care, The Second Affiliated Hospital of Anhui Medical University, Furong Road No. 678, Hefei, Anhui, 230032, People’s Republic of China, Email yangmin@ahmu.edu.cn Qiang Zhou, Department of Laboratory Medicine, The Second Affiliated Hospital of Anhui Medical University, Furong Road No. 678, Hefei, People’s Republic of China, Email Zhouqiang_ahmu@126.comPurpose: To establish and evaluate a simple disk stacking plus micro-elution (DSE) method that can be routinely performed to rapidly detect the synergistic effect between aztreonam (ATM) and ceftazidime/avibactam (CZA) against metallo-β-lactamase (MBL)-producing carbapenem-resistant Enterobacterales (CRE).Methods: The DSE method was established, and a total of 32 MBL-producing CRE isolates collected from multiple centers were tested for ATM-CZA synergy. The results obtained after 8 h of incubation were compared with those obtained by a reference checkerboard assay (CBA) after 18~24 h. Reproducibility experiments were completed on three separate days.Results: The reproducibility study showed that the results of the DSE method were precise. Compared with CBA, the DSE method exhibited excellent performance, with 92.8% sensitivity, 100.0% specificity 93.8% categorical agreement, 0.0% very major error, 0.0% major error, and 6.2% minor error over three days of testing.Conclusion: The DSE method is a simple, rapid and practical method for ATM-CZA combination testing. Further evaluation should be completed to improve its clinical application.Keywords: aztreonam, ceftazidime/avibactam, metallo-β-lactamases, Enterobacterales, antimicrobial combinations, clinical method